(untitled) (Management Dynamics, 2024)
Sustainable food security has become a key area of focus, highlighting the need to balance food availability with environmental preservation, economic sustainability, and social equity. This research assesses the effectiveness of systems supporting sustainable food security, aiming to identify successful strategies and challenges by reviewing existing policies, regulations, and consumer perceptions. A mixed-method approach was used, combining policy reviews, interviews, and survey data analysis, adapting a normative survey framework. The study encompasses three main components: the first evaluates policy provisions related to food availability, access, utilization, and stability; the second examines consumer perceptions of food security in Kathmandu; and the third proposes strategies to improve food security. The findings indicate that while policies and regulations align with global standards, their implementation remains ineffective. The study concludes that Nepalese policies and regulations align with global priorities; however, there are insufficient support mechanisms for sustainable food security in Kathmandu. The study offers immediate and long-term strategies to enhance food security in Kathmandu, considering the city’s emergency and average population growth rate.